Effectiveness of integrating sports training of students into the educational process of physical education university - Zakrevskaya N.G.; Medvedeva E.N.; Petrov S.I.; Terekhina R.N. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to to evaluate the effectiveness of the conditions for integrating sports training of students at physical education universities into the process of implementing the basis of a professional educational program in the direction of «Sport». Methods and structure of the study. Based on a generalization of monitoring data on the effectiveness of competitive and educational activities of students at the sports training center of NSU named after. P.F. Lesgafta, St. Petersburg in 2023, an assessment was made of the effectiveness of combining activities and the possibility of achieving high performance in solving pedagogical problems of a professional orientation. Results and conclusions. It has been established that increasing the effectiveness of professional training of sports teachers is achieved through the combination of activities that involve the development of both general and specific competencies of the future professional pedagogical activity of a sports teacher. Using the example of training female student athletes in rhythmic gymnastics, it was proven that the complementarity of functions performed by students when solving problems of educational, scientific and sports activities allows them to achieve high results in sports without reducing the quality of mastering the professional training program.